KEPUTUSAN PENGGUNAAN PRODUK KECANTIKAN PADA SANTRIWATI PESANTREN DI JOMBANG:PERSPEKTIF THEORY OF PLANNED BEHAVIOR - Ade Liya Wijayanti Wijayanti; Mohammad Haidar Ali (Fakultas Ekonomi, 2026)
The use of beauty products among female students (santriwati) in Islamic boarding schools has become an interesting phenomenon to study, as it occurs within a religious environment that upholds the values of simplicity while still showing a tendency toward the use of beauty products. This behavior is assumed to be influenced by psychological and social factors explained through the Theory of Planned Behavior (TPB), namely attitude, subjective norms, and perceived behavioral control toward intention and decision to use beauty products. This study aims to analyze the influence of attitude, subjective norms, and perceived behavioral control on the intention to use and the decision to use beauty products among female students in Islamic boarding schools in Jombang. This study employed a quantitative approach. The sample consisted of 230 respondents selected using a non-probability sampling technique with a purposive sampling method. Data were collected through questionnaires distributed to female students from four Islamic boarding schools in Jombang Regency. The data analysis technique used was Structural Equation Modeling-Partial Least Square (SEM-PLS) with the assistance of SmartPLS 4 software. The results showed that attitude, subjective norms, and perceived behavioral control had a positive and significant effect on the intention to use beauty products. In addition, the intention to use had a positive and significant effect on the decision to use, and perceived behavioral control also had a direct positive and significant effect on the decision to use beauty products among female students in Islamic boarding schools in Jombang. These findings indicate that the decision to use beauty products among female students is formed through the interaction of internal factors, social influence, perceived self-capability, and intention as the main driving factor in shaping usage behavior.